2022
DOI: 10.1186/s12885-022-09218-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of GnRH agonist treated GBM cell line LN229 revealed regulatory proteins inhibiting cancer cell proliferation

Abstract: Background Gonadotropin-releasing hormone (GnRH) receptor, a rhodopsin-like G-protein coupled receptor (GPCR) family member involved in GnRH signaling, is reported to be expressed in several tumors including glioblastoma multiforme (GBM), one of the most malignant and aggressive forms of primary brain tumors. However, the molecular targets associated with GnRH receptor are not well studied in GBM or in other cancers. The present study aims at investigating the effect of GnRH agonist (Gosarelin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…ITIH2 plays important roles in extracellular matrix stabilization and in the prevention of tumor metastasis ( 60 ). In addition, overexpression of the deregulated ITIH2 protein in glioma cells not only inhibits cancer cell invasion but also suppresses cell proliferation and promotes cell-cell adhesion ( 61 ). However, ITIH2 seemed to be a risk factor for patients with GC in our study, suggesting the need for more experiments.…”
Section: Discussionmentioning
confidence: 99%
“…ITIH2 plays important roles in extracellular matrix stabilization and in the prevention of tumor metastasis ( 60 ). In addition, overexpression of the deregulated ITIH2 protein in glioma cells not only inhibits cancer cell invasion but also suppresses cell proliferation and promotes cell-cell adhesion ( 61 ). However, ITIH2 seemed to be a risk factor for patients with GC in our study, suggesting the need for more experiments.…”
Section: Discussionmentioning
confidence: 99%
“…et al (2022) has revealed an overexpression of a cysteine proteinase inhibitor, KNG1, that inhibits cell proliferation and angiogenesis in response to GnRH agonists in glioma cells. This inhibition was also related to the breakdown of EGFR/PI3K/AKT signaling, 111,112 assuming a likely strong link between GnRH and EGFR signaling pathways via KNG1. In contrast, in our study, both KNG1 and lactotransferrin isoform 2 (LTF), preventing cancer development and metastasis, were downregulated.…”
Section: Potential Pathways Affected By the Selected Pesticide Mixturementioning
confidence: 95%
“…The blots were then incubated with secondary antibody (anti Rabbit-HRP, catalogue no. G-21234, 1/20,000) for 1 hr at RT and developed using the enhanced chemiluminescent (ECL) Kit (Millipore, USA) followed by image acquisition (24). The total density of the proteins in each lane was analyzed using densitometric analysis after SDS-PAGE analysis and was used for normalization (24).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…G-21234, 1/20,000) for 1 hr at RT and developed using the enhanced chemiluminescent (ECL) Kit (Millipore, USA) followed by image acquisition (24). The total density of the proteins in each lane was analyzed using densitometric analysis after SDS-PAGE analysis and was used for normalization (24). For quantitative analysis, the maximum density among GSD cases was considered to define the fold change in expression in individual GBC cases.…”
Section: Western Blot Analysismentioning
confidence: 99%